Endoscopic retrograd cholongiopancreatography results in diagnosis and therapy - Fatih HİLMİOĞLU; Bülent YILDIRIM; Melih KARINCAOĞLU; Murat ALADAĞ; Vildan TAŞKIN; Bülent KANTARÇEKEN (Turkish Journal of Gastroenterology, 2019)
-